2004
DOI: 10.1097/01.ta.0000114535.64175.c5
|View full text |Cite
|
Sign up to set email alerts
|

Can We Rely on Computed Tomographic Scanning to Diagnose Pulmonary Embolism in Critically Ill Surgical Patients?

Abstract: PA remains the "gold standard" for diagnosis of PE in critically ill surgical patients. CTPA should be explored further before being universally accepted. Clinical criteria are unreliable for detecting PE in this population and therefore a high index of suspicion should be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Following this selection process, 14 studies comparing spiral CT to PA [3,14,18–29] and four prospective pragmatic studies [6,30–32] remained for analysis; one additional prospective pragmatic study, initially published as an abstract, but subsequently in full was also included [7]. Agreement between both authors exceeded 95% of all extracted data; discrepancies were resolved by consensus.…”
Section: Resultsmentioning
confidence: 99%
“…Following this selection process, 14 studies comparing spiral CT to PA [3,14,18–29] and four prospective pragmatic studies [6,30–32] remained for analysis; one additional prospective pragmatic study, initially published as an abstract, but subsequently in full was also included [7]. Agreement between both authors exceeded 95% of all extracted data; discrepancies were resolved by consensus.…”
Section: Resultsmentioning
confidence: 99%
“…29 -31 Because of the potential hemorrhagic complications, many surgeons think that the use of anticoagulation in trauma patients is relatively contraindicated. 27,31 The ineffectiveness and complications of anticoagulant and mechanical prophylaxis have led to the "extended" or prophylactic use of VCFs. 6,10 Prophylactic VCFs have been associated with a reduction in symptomatic and fatal pulmonary emboli when compared with historic controls.…”
Section: Discussionmentioning
confidence: 99%
“…DVT occurs in up to 58% of severely injured patients, and PE causes up to 5% of deaths in trauma patients hospitalized for more than 48 hours. 1,3,26,27 Clinical and epidemiologic factors associated with increased risk of VTE after trauma include the following: age Ն40 years, Injury Severity Score Ͼ9, 23 lower extremity fracture, pelvic fracture, severe head injury, venous injury, vertebral fracture, or spinal cord injury. 2,7,9,10,28 The presence of more than one risk factor is associated with a significantly higher incidence of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…CT is another complementary modality that can help with non diagnostic studies in minimizing the number of patients undergoing pulmonary angiography. It is useful in detecting central emboli but data are controversial for peripheral emboli [33,34,35,37] Several studies have shown that this modality can not be reliable to withhold the anticoagulant therapy based on a negative spiral CT and it needs to be explored further before being accepted as a replacement for V/Q scans [38]. It was found that it has no added value in patients with high probability V/Q scans and has a comparable diagnostic value with SPECT V/Q scans [36].…”
Section: Spiralmentioning
confidence: 99%